The role of Nav 1.7 in human nociceptors: insights from human induced pluripotent stem cell-derived sensory neurons of erythromelalgia patients - Meents, Jannis; Bressan, Elisangela; Sontag, Stephanie; Foerster, Alec; Hautvast, Petra; Rösseler, Corinna; Hampl, Martin; Schüler, Herdit; Goetzke, Roman; Le, Thi Kim; Kleggetveit, Inge; Cann, Kim Le; et al. (Pain, 2019)
The chronic pain syndrome inherited erythromelalgia (IEM) is attributed to mutations in the voltage-gated sodium channel (NaV) 1.7. Still, recent studies targeting NaV1.7 in clinical trials have provided conflicting results. Here, we differentiated induced pluripotent stem cells from IEM patients with the NaV1.7/I848T mutation into sensory nociceptors. Action potentials in these IEM nociceptors displayed a decreased firing threshold, an enhanced upstroke, and afterhyperpolarization, all of which may explain the increased pain experienced by patients. Subsequently, we investigated the voltage dependence of the tetrodotoxin-sensitive NaV activation in these human sensory neurons using a specific prepulse voltage protocol. The IEM mutation induced a hyperpolarizing shift of NaV activation, which leads to activation of NaV1.7 at more negative potentials. Our results indicate that NaV1.7 is not active during subthreshold depolarizations, but that its activity defines the action potential threshold and contributes significantly to the action potential upstroke. Thus, our model system with induced pluripotent stem cell–derived sensory neurons provides a new rationale for NaV1.7 function and promises to be valuable as a translational tool to profile and develop more efficacious clinical analgesics.